The Design of Learning Methods for Reading Comprehension - Zulia Karini (IJECA (International Journal of Education and Curriculum Application), 2019)
The ability to read, in this case is the ability to understand English-language texts (reading comprehension), is one of the skills that must be possessed by students in a college. This relates to their academic activities that require them to struggle to find sources to support lecture activities. The number of reference sources is present in the form of articles, books, journals and proceedings which are often written in English. Interviews were conducted with several students of University of AMIKOM Purwokerto, Department of Informatics, finding out how to overcome the problem, and trying to provide alternative improvements. To overcome the difficulties experienced by students in reading English texts are by discussing a method of learning reading comprehension. This research is a descriptive study, which describes the facts of difficulties experienced by students in the difficulty of understanding the English text. The instrument used in data collection was a matter of English text. In this study, data analysis used consisted of three steps, namely data reduction, data presentation, and completing conclusions or verification.